Getting an Early Start on Early Child Development - Eming Young, Mary; Dunkelberg, Erika (World Bank, Washington, DC, 2012)
The children born this year, 2004, will be eleven years old in 2015-the age of primary school completion in most countries. This is the Millennium Development Goals (MDG) generation-for whom the international community has pledged that by 2015, all children will be able to complete primary schooling. Ensuring good early child development is the first essential step toward achieving these goals. The note reviews the benefits of early child development (ECD), its options, and coverage by country and region, and provides lessons as follows. A strong institutional framework should be complemented by local capacity, and community participation, while ECD programs should be federally funded. Monitoring and evaluation mechanisms should be in place, as an interactive process, responsive to local needs, and for effective outcomes.